Výživa obyvateľstva Slovenska v období budovania socializmu - Stoličná, Rastislava (Studia Etnologiczne i Antropologiczne, 2021)
The study aims to describe the most important changes in public nutrition during socialism in Slovakia. It explains the essence of the state Communist ideology’s involvement in people’s eating habits and the reality of socialist food production and distribution in the 1950s, when the acquirement of even basic foodstuffs was often accompanied by food shortage, bad quality, time losses related to food acquirement and high prices in some cases.